Predicting Interest in Islamic Banking Services: The Roles of Islamic Financial Literacy, Religiosity, and Perception with Accounting Information as a Moderator - Retno Anjani; Agus Maulana (Syi`ar Iqtishadi : Journal of Islamic Economics, Finance and Banking, 2025)
Drawing on the Theory of Reasoned Goal Pursuit (TRGP), this study examines how Islamic financial literacy, religiosity, and perception shape customer interest in Islamic banking services, and assesses whether accounting information moderates these relationships. This research addresses a gap in prior studies that have rarely integrated TRGP with cognitive and religious factors while also considering the role of accounting information. Data were collected from 233 Islamic bank customers in Jabodetabek and analyzed using SEM-PLS with SmartPLS 4. The results show that Islamic financial literacy, religiosity, and perception positively influence interest in Islamic banking, whereas accounting information does not moderate these effects. The study contributes theoretically by extending TRGP into the context of Islamic financial behavior and empirically by providing evidence from a major Indonesian region. Practical implications highlight the need for Islamic banks to strengthen financial literacy initiatives and enhance customer perceptions to increase interest in Islamic banking services.